Acute thrombogenicity of fluoropolymer coated stents versus competitive drug-eluting stents under single antiplatelet therapy. (1st September 2021) - Sato, Yu; Jinnouchi, Hiroyuki; Kolodgie, Frank D.; Cheng, Qi; Janifer, Christine; Kutyna, Matthew; Sakamoto, Atsushi; Cornelissen, Anne; Mori, Masayuki; Kawakami, Rika; Kawai, Kenji; Fernandez, Raquel; et al.
Abstract: Background: Recent clinical studies have suggested the feasibility of 1-month dual antiplatelet therapy (DAPT) for patients receiving drug-eluting stent (DES). Although our previous ex-vivo swine arteriovenous (AV) shunt studies under low dose heparin treatment suggested superior thromboresistance of fluoropolymer-coated everolimus-eluting stent (FP-EES) when compared to other polymer-based DESs, the relative thromboresistance of different DESs under single antiplatelet therapy (SAPT) has never been examined. This study aimed to evaluate platelet adhesion under SAPT in competitive DESs in the in vitro flow loop model and ex vivo swine AV shunt model. Methods: The thrombogenicity of FP-EES, BioLinx polymer zotarolimus-eluting stent (BL-ZES), and biodegradable polymer everolimus-eluting stent (BP-EES) was assessed acutely using the swine AV shunt model under aspirin or clopidogrel SAPT. Stents were immunostained using antibodies against platelets and inflammatory markers and evaluated by confocal microscopy. Also, the adhesion of platelet and albumin on the three DESs was assessed by an in-vitro flow loop model using human platelets under aspirin SAPT and fluorescent albumin, respectively. Results: In the shunt model, FP-EES showed significantly less platelet and inflammatory cell adhesion than BL-ZES and BP-EES. In the flow loop model, FP-EES showed significantly less platelet coverage and more albumin adsorption than BL-ZES and BP-EES. Conclusions: These results suggest FP-EES may have particular advantage for short-term DAPT compared to other DESs. Highlights: Recent studies suggest feasibility of short-term DAPT for patients receiving DES. The relative thromboresistance of different DESs under SAPT has never been examined. We compared thrombogenicity in current contemporary DESs. An in vitro flow loop model and ex vivo swine AV shunt model on SAPT were performed. Fluoropolymer-coated DES showed superior thromboresistance than other DESs on SAPT.